The missing study: a characterization of peer education practice - Silva, M. F.; Matos, A. D.; Henriques, S. (Sociologia, Problemas e Práticas, 2021)
Peer education interventions have grown significantly in recent decades, but sociological studies on the subject are limited. To respond to this need, we carried out an exhaustive inventory and characterization of 67 peer education projects developed in Portugal. The information given by the project managers was processed using a content analysis technique. This practice is growing, benefiting from public and private promotion. Although it has demonstrated some efficacy, further improvements can be made. The characterization undertaken allowed us to build a typology that summarizes this practice and that can be useful for researchers and practitioners in a context of globalization of risks and increased social intervention and reflexivity.